Evaluation on electronic submission assessment grading assignment (e-SAGA) using technology acceptance model (TAM) / Mohd Amli Abdullah @ Baharum … [et al.] - Abdullah @ Baharum, Mohd Amli; Akmal Saad, Zuria; Mohd Mokhtar, Noorsuraya; Abu Bakar, Suwaibah (2015)
Technology plays a major role in teaching and learning. Student assignment is part of the process. In this study, the researcher focuses on acceptance of the lecturers on using E-saga process by using TAM Model. 98 respondents from UiTM Pahang name list were selected randomly to answer questionnaires. The descriptive and inferential statistics were employed in analyzing the data and answering the research questions of the study. Frequency of distribution and measure central tendency were used in presenting and summarizing the data, Descriptive statistics such as means, standard deviation and percentage appropriate were used to describe research questions of the study. The results of the study demonstrated that some TAM constructs had a direct and indirect effect on users' behavioral intention to use e-SAGA. For that reason, there is potential for practical application in the development and management of e-SAGA in UiTM.